EAS Cherenkov LDF Analysis: CORSIKA Simulations for Tunka-133 and Chacaltaya Arrays - Kadhom F. Fadhel; A. A. Al-Rubaiee (Academia Open, 2024)
This study leverages CORSIKA simulations to analyze the Lateral Distribution Function (LDF) of Cherenkov photons in Extensive Air Showers (EAS) within the knee region of the cosmic ray energy spectrum (10^15 - 10^16 eV). Focusing on primary particles like helium, proton, oxygen, and iron nuclei at varying zenith angles (0˚, 20˚, and 45˚), we aimed to reconstruct Cherenkov photons' LDF using an Exponential Function model, tailored as a function of primary energy. Our approach involved a comparative analysis of simulated LDFs with experimental data from the Tunka-133 and Chacaltaya arrays. The results exhibit a high degree of concordance between simulated and observed data, affirming the validity of our method. We developed a set of approximation functions for different primary particles and zenith angles, enhancing our ability to identify the particle type in EAS events and accurately determine its energy. The primary contribution of our work lies in its potential to rapidly compile a comprehensive LDF pattern library, instrumental for analyzing real EAS array events and reconstructing the mass composition and primary cosmic ray energy spectrum. This advancement in CORSIKA-based simulation methods marks a significant stride in cosmic ray research, offering a robust tool for detailed EAS analysis.Highlights : Validation of Simulation Accuracy: Demonstrated high concordance between CORSIKA simulated LDFs and experimental data from Tunka-133 and Chacaltaya arrays. Enhanced Particle Identification: Development of approximation functions for various primary particles and zenith angles, improving accuracy in identifying particle types in EAS events. Advancement in Cosmic Ray Research: Potential to create a comprehensive LDF pattern library, significantly aiding in the reconstruction of mass composition and primary cosmic ray energy spectrum. Keywords : CORSIKA Simulations, Cherenkov LDF, EAS Analysis, Cosmic Ray Spectrum, Particle Identification